If it's not what You are looking for type in the equation solver your own equation and let us solve it.
42=3(-3-3h)
We move all terms to the left:
42-(3(-3-3h))=0
We add all the numbers together, and all the variables
-(3(-3h-3))+42=0
We calculate terms in parentheses: -(3(-3h-3)), so:We get rid of parentheses
3(-3h-3)
We multiply parentheses
-9h-9
Back to the equation:
-(-9h-9)
9h+9+42=0
We add all the numbers together, and all the variables
9h+51=0
We move all terms containing h to the left, all other terms to the right
9h=-51
h=-51/9
h=-5+2/3
| 7m-17=15 | | x4−8=3 | | .1x-x=2790 | | 20+6x+16=180-90 | | x+2/12=1/6=x-3/4 | | 0.4j=-20 | | 11+x=385 | | (x.10)-x=2790 | | x+2/6=8/3+x-3/2 | | -12x-10=13x+16 | | (3x-10)+(3x-10)+(2x)+(2x)+(3x+6)=180 | | -12x-10=-13x+16 | | H=-16t^2+122t+5 | | /7m-2-6/7m=-13 | | 5/7m-2-6/5m=-13 | | -55-6x=45-11x | | -9x-24=-12x+39 | | m/7=3/8 | | –19p+19+6p=–8p+4 | | x-37=98 | | 8x-81=144-x | | Z+4z=6 | | 2n+10=-2n+10 | | -167-4x=-11x+85 | | 2(n+5)=-2n+10 | | -144=8(v-10) | | 3x-164=136-12x | | 4n^2+8n+8=0 | | x=133.33 | | 30+3w=90 | | -71+x=-5x+61 | | F(-2)=8x+3 |